Genocide, Extinction and Aboriginal Self‐determination in Tasmanian Historiography. Issue 6 (10th June 2013) - Taylor, Rebe
Abstract The principal aim of this article is to survey the long and complex relationship between the ideas of genocide and extinction as they apply to Tasmanian historiography from the colonial period to the present moment. In so, doing this essay brings up to date Ann Curthoys' 2008 essay on genocide in Tasmania and extends Curthoys' principal inquiry: how there emerged 'a paradox' between international representations of Tasmania as a 'clear‐cut' case of genocide and the fact 'such a characterization is rarely adopted within Australia'. This essay finds Curthoys' 'paradox' less relevant to popular Australian representations of Tasmanian history where, from the 1970s, the idea of genocide did not merely replace the older idea of extinction, but promulgated it. Such representations directly undermined an emergent movement for Tasmanian Aboriginal self‐determination. The political protest of Tasmanian Aboriginal people influenced historical scholarship, lead foremost by Lyndall Ryan from the early 1980s: to characterize Tasmania as a case of genocide at that time may have potentially jeopardized an important message of Aboriginal survival in the face of colonialism.